Metagenome Survey of Biofilms in Drinking-Water Networks - Schmeisser, C. (American Society for Microbiology, 2003)
Most naturally occurring biofilms contain a vast majority of microorganisms which have not yet been cultured, and therefore we have little information on the genetic information content of these communities. Therefore, we initiated work to characterize the complex metagenome of model drinking water biofilms grown on rubber-coated valves by employing three different strategies. First, a sequence analysis of 650 16S rRNA clones indicated a high diversity within the biofilm communities, with the majority of the microbes being closely related to the Proteobacteria. Only a small fraction of the 16S rRNA sequences were highly similar to rRNA sequences from Actinobacteria, low-G+C gram-positives and the Cytophaga-Flavobacterium-Bacteroides group. Our second strategy included a snapshot genome sequencing approach. Homology searches in public databases with 5,000 random sequence clones from a small insert library resulted in the identification of 2,200 putative protein-coding sequences, of which 1,026 could be classified into functional groups. Similarity analyses indicated that significant fractions of the genes and proteins identified were highly similar to known proteins observed in the genera Rhizobium, Pseudomonas, and Escherichia. Finally, we report 144 kb of DNA sequence information from four selected cosmid clones, of which two formed a 75-kb overlapping contig. The majority of the proteins identified by whole-cosmid sequencing probably originated from microbes closely related to the alpha-, beta-, and gamma-Proteobacteria. The sequence information was used to set up a database containing the phylogenetic and genomic information on this model microbial community. Concerning the potential health risk of the microbial community studied, no DNA or protein sequences directly linked to pathogenic traits were identified.